The Correlation Between Teachers’ Strategies in Using Audiovisual Media and Students’ Interest Toward Listening Comprehension Achievement - Andini, Tri; Hadiyanto, Hadiyanto; Masbirorotni, Masbirorotni (Universitas Jambi, Magister Program of English Education Department, 2025)
This study aims to determine the correlation between teachers’ strategies in using audiovisual media and students’ interest in listening comprehension achievement. The research used a quantitative method with a correlational design. The participants of this study were second- and fourth-semester students of the English Education Study Program in 2025 at the University of Jambi. Data were collected through a questionnaire using a Google Form. This research aimed to see whether teachers' use of audiovisual media could improve students’ interest and performance in listening skills. The results showed that students who believed their teachers used interesting and effective audiovisual strategies were more interested in listening activities. The study also found a positive relationship between how teachers used media and the students’ listening comprehension scores. On the other hand, students who thought listening was difficult tended to get lower scores. Although students felt interested and saw the benefits of audiovisual media, these two factors did not directly affect their listening comprehension scores. This research highlights the importance of good teaching strategies to help students become more motivated and improve their listening skills.